1986
DOI: 10.1128/aac.30.1.192
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by levamisole, methisoprinol, and adenine or adenosine of the inhibitory activity of human interferon against encephalomyocarditis virus

Abstract: The antiviral action of different human interferons against encephalomyocarditis virus in HeLa cell cultures was analyzed. Cell treatment with levamisole (200 ,ug/ml), methisoprinol (1 mg/ml), or adenine or adenosine (33 or 100 ,g/ml, respectively) potentiated the anti-encephalomyocarditis virus activity of human interferon by 8-to 32-fold. A higher level of potentiation (256-fold) was achieved either by combined treatments with levamisole plus methisoprinol or by treatment with one of these compounds plus ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Kimball and his associates (26) showed also that oral administration of levamisole to mice results in a twofold increase of IL‐1 production by their peritoneal macrophages stimulated in the presence of lipopolysaccaride. The possibility of biologic modulation is also supported by the finding that levamisole potentiates the activity of human interferon and IL‐2 (27,28).…”
Section: Discussionmentioning
confidence: 91%
“…Kimball and his associates (26) showed also that oral administration of levamisole to mice results in a twofold increase of IL‐1 production by their peritoneal macrophages stimulated in the presence of lipopolysaccaride. The possibility of biologic modulation is also supported by the finding that levamisole potentiates the activity of human interferon and IL‐2 (27,28).…”
Section: Discussionmentioning
confidence: 91%
“…5 Levamisole increases serum levels of interleukin-2 receptor in patients with cancer 6 and potentiates the production interferon and interleukin-2 in humans. 7,8 In normal mice, levamisole is not directly toxic to myelin. However, when administered to mice infected with a demyelination-inducing virus (Theiler's virus), demyelination and inflammation are augmented and accelerated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that levamisole stimulates T cells or macrophages; in addition, it restores delayed hypersensitive reactions in immune‐depressed patients 34 . Recent studies have reported that levamisole increases serum levels of IL‐2 receptors in patients with cancer 35 and IL‐1 production in mice models 36 . Levamisole is metabolized by the liver and then secreted from the kidney; no clearance by haemodialysis or peritoneal dialysis has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%